Modeling of steady state and transient state of the power electronic distribution transformer - Ahmed, K.Y. (Springer Verlag, 2017)
This research study presents a new type of power electronic distribution transformer (PEDT), aimed to overcome the disadvantages of the traditional electromagnetic distribution transformers. This new proposed model is named as power electronic distribution transformer incorporating power electronic converters in both primary and secondary sides, in addition to the high-frequency transformer. Moreover, the PEDT is capable of providing many advantages, such as power factor improvement, voltage sag/swell, reactive power compensation, harmonics elimination, self-protection and size reduction as compared to the conventional electromagnetic transformer. MATLAB/Simulink is used to simulate the proposed model. The simulation results show that the model is capable of offering an additional DC bus on the primary side as well as high power conversation ratios and power quality improvement. © Springer Science+Business Media Singapore 2017.